-r+6=43

Simple and best practice solution for -r+6=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -r+6=43 equation:


Simplifying
-1r + 6 = 43

Reorder the terms:
6 + -1r = 43

Solving
6 + -1r = 43

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1r = 43 + -6

Combine like terms: 6 + -6 = 0
0 + -1r = 43 + -6
-1r = 43 + -6

Combine like terms: 43 + -6 = 37
-1r = 37

Divide each side by '-1'.
r = -37

Simplifying
r = -37

See similar equations:

| -x-4=3x-16 | | 1x+8y=150 | | 46m^4=2m^2n | | 4y*3y*y= | | 0=20x^3+9x^2-8x-2 | | 3t^2+11t+6= | | 3=3x-4x+2 | | 7z-35=35 | | 21x^2-40x-21=equation | | 46gh=6g^3h^6 | | e^2x-1=18 | | 26x^2-19xy+3y^2=equation | | 4x+12=3+4x | | 2/3x-1=-3x/4 | | -12+x=-9 | | 21x^3=28x^5 | | f(x)=6x^-8/3-2x^-2/3 | | X+2y-20=0 | | -5(6x+1)=55 | | -2x+13+4x+13=2 | | -y/3=-18 | | x^2+144x+2659=0 | | 48a^6=38a | | 9x^4-279x^2-2396=0 | | -x-3x=6 | | 7p=228 | | 0=20x^3+6x-2 | | M/3=-9 | | -3y-7=-10-6y-6y | | 9+9=45-9x | | f(x)2x^2+4x+1= | | 3(x-6)-2x=32 |

Equations solver categories